Influence of Caribbean eddies on the Loop current system evolution - Ntaganou, Nektaria; Kourafalou, Vassiliki; Beron-Vera, Francisco Javier; Olascoaga, Maria Josefina; Le Hénaff, Matthieu; Androulidakis, Yannis (Frontiers in Marine Science, 2023)
The Loop Current (LC) system dynamics are an essential component of the processes influencing circulation and transport in the Gulf of Mexico (GoM). The LC evolution is influenced by various factors, including the rich eddy field of the region and the flow exchange through the Yucatan Strait with the neighboring Caribbean Sea. These factors contribute to the complexity of the LC and, as a result, to the limitations in the predictability of the system. The focus of this study is to further elucidate the evolution of the LC, by quantifying the influence of coherent eddy fluxes originating in the Caribbean Sea. This is achieved by employing the Lagrangian-Averaged Vorticity Deviation (LAVD) method, an objective metric to evaluate eddy coherence in the Caribbean Sea that allows, for the first time, to quantify at different depths the evolution of coherent Caribbean eddies through the Yucatan Channel towards the GoM. The physical connectivity between the Caribbean Sea and the GoM is addressed using Lagrangian techniques to analyze processes that take place south of the Yucatan Channel and help quantify their strong relationship with the GoM eddy field. Coherent anticyclonic vorticity fluxes, as well as the net coherent anticyclonic volume transport between the Caribbean Sea and the GoM are associated with Loop Current Eddy (LCE) detachments through direct connectivity between the coherent Caribbean anticyclones and the forming LCE. The findings have important implications for understanding and predicting the LC system and the physical connectivity processes between the GoM and the Caribbean Sea.